2021
DOI: 10.5194/amt-14-5241-2021
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the coupled high-resolution atmospheric chemistry model system MECO(n) using in situ and MAX-DOAS NO<sub>2</sub> measurements

Abstract: Abstract. We present high spatial resolution (up to 2.2×2.2 km2) simulations focussed over south-west Germany using the online coupled regional atmospheric chemistry model system MECO(n) (MESSy-fied ECHAM and COSMO models nested n times). Numerical simulation of nitrogen dioxide (NO2) surface volume mixing ratios (VMRs) are compared to in situ measurements from a network with 193 locations including background, traffic-adjacent and industrial stations to investigate the model's performance in simulating the sp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 72 publications
1
4
0
Order By: Relevance
“…This suggests that the scatter in MAX-DOAS versus in situ measurements is to some degree dominated by spatial averaging effects. Although to our knowledge there is no other study comparing vertical and slant columns with in situ measurements simultaneously, our finding is supported by [43] who used in situ and MAX-DOAS NO 2 measurements to evaluate an atmospheric chemistry model. They showed that slant columns are more suitable for such a comparison because they account for the horizontal heterogeneity in the viewing direction in contrast to vertical columns, the retrievals of which involve more uncertainties and complexity.…”
Section: Comparisons With In Situ Observationssupporting
confidence: 79%
“…This suggests that the scatter in MAX-DOAS versus in situ measurements is to some degree dominated by spatial averaging effects. Although to our knowledge there is no other study comparing vertical and slant columns with in situ measurements simultaneously, our finding is supported by [43] who used in situ and MAX-DOAS NO 2 measurements to evaluate an atmospheric chemistry model. They showed that slant columns are more suitable for such a comparison because they account for the horizontal heterogeneity in the viewing direction in contrast to vertical columns, the retrievals of which involve more uncertainties and complexity.…”
Section: Comparisons With In Situ Observationssupporting
confidence: 79%
“…Due to the short lifetime of NO x the observed concentrations closely follow the temporal profiles. As an initial starting point, the temporal profiles from Kumar et al (2021) were used. Although the proposed optimization method is rather unconventional, it has a few important benefits.…”
Section: Optimization Of Temporal Profilesmentioning
confidence: 99%
“…Figure 2h reveals that the overall NO x budget assumed for the simulated month is realistic, meaning that the corresponding monthly weighting factor is reasonable. Similarly, the daily profiles from Kumar et al (2021) were taken over without changes. What remains are the hourly profiles of each sector.…”
Section: Optimization Of Temporal Profilesmentioning
confidence: 99%
See 2 more Smart Citations